GATA1s induces hyperproliferation of eosinophil precursors in Down syndrome transient leukemia - Maroz, A; Stachorski, L; Emmrich, S; Reinhardt, K; Xu, J; Shao, Z; Käbler, S; Dertmann, T; Hitzler, J; Roberts, I; Vyas, P; Juban, G; et al. (Nature Publishing Group, 2014)
Transient leukemia (TL) is evident in 5-10% of all neonates with Down syndrome (DS) and associated with N-terminal truncating GATA1 mutations (GATA1s). Here we report that TL-cell clones generate abundant eosinophils in a substantial fraction of patients. Sorted eosinophils from patients with TL and eosinophilia carried the same GATA1s mutations as sorted TL blasts, consistent with their clonal origin. TL blasts exhibited a genetic program characteristic of eosinophils and differentiated along the eosinophil lineage in vitro. Similarly, ectopic expression of Gata1s, but not Gata1, in wild-type CD34 + -hematopoietic stem and progenitor cells induced hyperproliferation of eosinophil promyelocytes in vitro. Although GATA1s retained the function of GATA1 to induce eosinophil genes by occupying their promoter regions, GATA1s was impaired in its ability to repress oncogenic MYC and the pro-proliferative E2F transcription network. Chromatin Immunoprecipitation Sequencing (ChIP-seq) indicated reduced GATA1s occupancy at the MYC promoter. Knockdown of MYC, or the obligate E2F-cooperation partner DP1, rescued the GATA1s-induced hyperproliferative phenotype. In agreement, terminal eosinophil maturation was blocked in Gata1 Δe2 knockin mice, exclusively expressing Gata1s, leading to accumulation of eosinophil precursors in blood and bone marrow. These data suggest a direct relationship between the N-terminal truncating mutations of GATA1 and clonal eosinophilia in DS patients. © 2014 Macmillan Publishers Limited.